Conscious and Unconscious Responses as Independent Components of a Person’s Current Psychophysiological State - Minkin, Viktor A.; Myasnikova, Ekaterina M.; Nikolaenko, Yana N. (International Journal of Psychosocial Rehabilitation, 2020)
A person’s conscious and unconscious responses are defined in reaction to the presentation of oppositional stimuli in the process of testing multiple intelligences. The unconscious response is measured with the use of vibraimage technology, which allows quantifying the psychophysiological state. The aim of the article is to show the feasibility of using the periodic presentation of opposite stimuli to control a person’s psychophysiological state. Materials and methods: Organizational, empirical, and statistical methods used for the study of 574 people aged 14 to 55 years of the humanities and classical technical specialties and from different countries. The developed methodology allows one to jointly analyze the process of conscious and unconscious responses, reducing them to a single characteristic of personality or psychophysiological state. Results: It was established that conscious and unconscious responses complement each other in the absence of intercorrelation. The proven lack of correlation between a person’s conscious and unconscious response to a stimulus is direct evidence of the ability to conscientiously process these reactions, which is the basis for obtaining the multiple intelligence profile. The identified dependence of psychophysiological control allows one to reconsider the practical methods of conducting interviews and surveys, as well as the prediction of abilities, lie detection, and the more effective choice of stimuli sequences when conducting profiling. Conclusion: The high efficiency of the vibraimage technology demonstrates that the conscious and unconscious responses complement each other and do not correlate with each other. The cybernetic approach to a person allows bringing humanity to a new stage of evolution and understanding of its place in physical nature., unconscious.